Acquired lymphedema: Molecular contributors and future directions for developing intervention strategies - Nurlaila, Ika; Roh, Kangsan; Yeom, Chang-Hwan; Kang, Hee; Lee, Sukchan (Frontiers in Pharmacology, 2022)
Lymphedema is a debilitating chronic disease that mostly develops as an adverse reaction to cancer treatment modalities such as chemotherapy, surgery, and radiotherapy. Lymphedema also appears to be a deteriorating consequence of roundworm infections, as best represented by filariasis. According to its origin, lymphedema is classified as primary lymphedema and acquired lymphedema. The latter is an acquired condition that, hitherto, received a considerably low attention owing to the less number of fatal cases been reported. Notably, despite the low mortality rate in lymphedema, it has been widely reported to reduce the disease-free survival and thus the quality of life of affected patients. Hence, in this review, we focused on acquired lymphedema and orchestration of molecular interplays associated with either stimulation or inhibition of lymphedema development that were, in vast majority, clearly depicted in animal models with their specific and distinct technical approaches. We also discussed some recent progress made in phytochemical-based anti-lymphedema intervention strategies and the specific mechanisms underlying their anti-lymphedema properties. This review is crucial to understand not only the comprehensive aspects of the disease but also the future directions of the intervention strategies that can address the quality of life of affected patients rather than alleviating apparent symptoms only.